HERRAMIENTAS INFORMÁTICAS: USO EN PROCESOS DE ENSEÑANZA-APRENDIZAJE DE ENTORNOS VIRTUALES - Marisa Cecilia Tumino; Juan Manuel Bournissen (European Scientific Journal, ESJ, 2014)
The purpose of the present study is to investigate virtual tools which allow the implementation of teaching strategies that facilitate meaningful learning within a virtual platform. Thestudyalsoidentifies the strategies employed by teachers who use a virtual campus at a private university in Argentina. The intent of the study is to determine if there are patterns of use of virtual tools or teaching strategies related to different variables, such as the discipline or the training received. The study explores the tools that worked well with the strategies implemented by teachers. Ultimately, the results of this study can help a significant number of teachers of the institution to gain access to the challenging trends proposed by virtual information technology.